The Development of a Writing Course for Engineers at Vietnam Atomic Energy Institute Using Competence-based Approach - Trang, Pham Thi Thu; Mai, Duong Thu (VNU Journal of Science: Education Research; Vol 33 No 1, 2017)
Abstract: Strong needs of working learners, urgent demands of the occupation and great expectation of leaders have revealed an immediate call for designing a writing course at Vietnam Atomic Energy Institute (VAEI). At the same time, the use of competence-based approach so that the learning outcomes can meet future staffing requirements of the organization has emerged as advantageous over other approaches of course design. In this case, based on VAEI contexts, learners’ needs and employers’ requirements analysis, the paper is to explore the target genres, determine the specificity of writing competences covered within the course, and then develop a competence-based course schedules. Notably, there have been no attempts in investigating this issue before. Hopefully, the paper would not only present a needed course for engineers at VAEI but also provide suggestions for the course design and implementation in the light of Competence-Based Approach. Keywords Higher education, higher education development policy, university autonomy References [1] Molina, G. T., Cañado, M. L. P. & Agulló, G. L., Current Approaches And Teaching Methods. Bilingual Programmes. Granada: TEFL in Secondary Education, Editorial Universidad de Granada, 2005. [2] Anderson, G. S., A Whole Language Approach to Reading. Lanham, MS: University Press of America, 1984. [3] White, R. W., The ELT curriculum. Oxford: Basil Blackwell, 1988. [4] Widdowson, H. J., Teaching Language as Communication. Oxford University Press, 1979. [5] Kouwenhoven, W., Competence-Based Curriculum Development In Higher Education: A Globalised Concept. The Netherlands: VU University Amsterdam, 2003. [6] Field, L. & Drysdale, D., Training For Competence: A Handbook For Trainers And Teachers. London: Kogan Page, 1991. [7] Richards, J. C., Curriculum development in language teaching. UK: Cambridge University Press, 2001. [8] Chinh, C. D., Teaching on Competency - Based Approach at Technical Education Universities, Phylosophy Doctor Thesis, Vietnam National Library, 2012. [9] Nunan, D., Standard-based approaches to the evaluation of ESL instruction. International Handbook of English Language Teaching, 15 (2007), 421-438. [10] Gustafson, K. L. & Branch, R. M., Survey of Instructional Development Models. New York: Eric Clearing House on Information & Technology, 2002. [11] Graves, K., Teachers as Course Developers. New York: Cambridge University Press, 1996. [12] Kemp, J., Morrison, G., & Ross, S., Designing Effective Instruction (2nd Ed.). New York: Merill, 1998. [13] Greer, M., The project mangager’s partner: A step-by-step guide to project management. Amherst, MA: HRD Press, 1996. [14] Dick, W. & Carey, L., The Systematic Design Of Instruction (4th Ed.). New York: Harper Collins, 1996. [15] Đại học Quốc Gia Hà Nội, Hướng dẫn xây dựng và hoàn thiện chương trình đào tạo theo chuẩn đầu ra, 2010. [16] Council of Europe, Using the CEFR: Principles of Good Practice. University of Cambridge, 2001. [17] Tribble, C., Writing. New York: Oxford University Press, 1996. Gregg, J. & Steinberg, E.R., Cognitive in applied Education. Oxford: Oxford University Press, 1985.